Tautomycetin Induces Apoptosis by Inactivating Akt Through a PP1-Independent Signaling Pathway in Human Breast Cancer Cells - Mingshan Niu; Yan Sun; Xuejiao Liu; Li Tang; Rongguo Qiu (Elsevier, 2013)
Tautomycetin (TMC), originally isolated from Streptomyces griseochromogenes, has been suggested as a potential drug retaining specificity toward colorectal cancer. However, we found that TMC exhibited inhibitory effects on cell proliferation of many cancer cell lines including adriamycin-resistant human breast adenocarcinoma. We investigated its anti-tumor activity and mechanisms in human breast cancer cells for the first time. In this study, we showed that TMC effectively inhibited breast cancer cell proliferation, migration, and invasion. TMC also induced apoptosis in MCF-7 cells. This apoptotic response was in part mediated by Bcl-2 cleavage, leading to the release of cytochrome c, which facilitates binding of Apaf-1 to caspase-9 in its presence and subsequent activation of caspase-7 in apoptosis induction signaling pathways. Furthermore, we identified that TMC induced apoptosis by suppressing Akt signaling pathway activation, which is independent of protein phosphatase PP1 inhibition. The levels of downstream targets of Akt, including phospho-forkhead transcription factor and Bad, were also reduced after TMC treatment. Overall, our results indicate that TMC could be used as a potential drug candidate for breast cancer therapy. More importantly, our study provides new mechanisms for the anticancer effects of TMC. Keywords:: tautomycetin, apoptosis, breast cancer, Akt pathway